The Influence of Immunization Counseling Module Using Stickers on Toddler’s Mother Behavior about Advanced Immunization (Booster) - Nurhayati Nurhayati; Sudiyati Sudiyati; Erlin Puspita; Siti Rahmadani (Humanistic Network for Science and Technology (HNST), 2020)
In Indonesia, the coverage of the immunization is still low and the incidence of diseases caused by not having DPT-HB-Hib immunization is still high. The purpose of this study was to determine the influence of immunization counseling using stickers on toddler’s mother behavior about advanced immunization (booster). The design of this study was a pretest and post test with a control group. The population in this study were all mothers who had toddlers aged 12-24 months in the integrated health service center area of Depok City with a sample of 60 mothers divided into 2 groups. The results showed that there were differences in knowledge (p-value = 0.011) and actions (p-value = 0.036) in the intervention and the control group after immunization counseling using a counseling module and stickers. Based on the results, there is influence of knowledge on maternal behavior about advanced immunization in toddlers. Keywords: advanced immunization; maternal behavior; counseling